Peningkatan Kompetensi Literasi Calis dan Numerasi Mahasiswa PGSD Universitas Satya Wiyata Mandala melalui Pelatihan Berbasis Praktik - Winda Woro Mahmudah; Santji Afi Rangkoly; Tut Hidayatillah; Rivaldo Paul Telussa; Jasmari Jasmari; Jermanto Subeno Lasamahu (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Strengthening reading–writing literacy and numeracy has become a strategic priority in primary education, particularly in preparing prospective teachers who are capable of integrating these competencies contextually into classroom practice. This community engagement program aimed to enhance the conceptual understanding, pedagogical skills, and professional readiness of students from the Primary School Teacher Education Program (PGSD) at Universitas Satya Wiyata Mandala (USWIM) Nabire through a practice-based literacy and numeracy training model. The program was conducted over three days and involved 100 active students. The training adopted a practice-based approach consisting of conceptual reinforcement sessions, group discussions, lesson plan development, and microteaching simulations. Data were collected through observation, analysis of instructional materials, and written reflections, and analyzed using a descriptive qualitative approach. The findings indicate a significant shift in students’ understanding of literacy and numeracy—from technical skills to contextual and reasoning-based competencies. Participants demonstrated improved ability to design literacy–numeracy-based lesson plans and delivered more dialogic and participatory microteaching sessions. The program also fostered stronger professional awareness regarding the role of teachers in building foundational literacy and numeracy skills in primary education. Overall, the practice-based training proved effective in strengthening the professional preparedness of prospective primary school teachers in a contextual and systematic manner.